Effects of Tembotrione on Potato Crop in a Tropical Soil - Dias, Roque de Carvalho [UNESP]; Melo, Christiane Augusta Diniz; Faria, Autieres Teixeira; Silva, Daniel Valadão; Ferreira Mendes, Kassio; dos Reis, Marcelo Rodrigues (Taylor & Francis, 2019)
Tembotrione is an herbicide with a high persistence in soil, a characteristic that affects the growth and development of susceptible cultures in succession. In this sense, the objective of this research was to evaluate the residual effects of tembotrione on production and quality of potato tubers in a tropical soil. A field experiment (2014/2015) with randomized blocks design with four replications was conducted. The treatments consisted of five doses of tembotrione (0, 8.4, 16.8, 33.6, and 50.4 g a.i. ha−1) incorporated into the soil before planting the potato cultivar Atlantic. At 115 days after herbicide application were evaluated: total solids (%), dry matter content (DMCT %), nitrogen and potassium of the tubers, total yield and classification. The productivity of normal tubers decreased as doses of tembotrione were increased. The percentage of class I tubers was reduced at doses of 33.6 and 50.4 g a.i. ha−1. The increase in the doses increased the percentage of class II tubers and did not influence the percentage of class III and discard. The appearance of cracked tubers increased with increasing herbicide doses. Tembotrione affected the productivity of potato tubers and caused cracks in the tubers, which are dependent on the applied doses.
Keywords: Carryover; crack; phytotoxicity; soil persistence; Solanum tuberosum L